Codesign Lessons Learned from Implementing Graph Matching on Multithreaded Architectures - Halappanavar, Mahantesh; Pothen, Alex; Azad, Ariful; Manne, Fredrik; Langguth, Johannes; Khan, Arif (Computer (Long Beach, Calif.), 2015)
Executing irregular, data-intensive workloads on multithreaded architectures can result in performance losses and scalability problems. Codesigning algorithms and architectures can realize high performance on irregular applications. A codesign study reveals four key lessons learned from implementing matching algorithms on various platforms.